Information Security Management Handbook, Sixth Edition - Tipton, Harold (CRC Press, 2009)
Never before have there been so many laws designed to keep corporations honest. New laws and regulations force companies to develop stronger ethics policies and the shareholders themselves are holding publicly traded companies accountable for their practices. Consumers are also concerned over the privacy of their personal information and current and emerging legislation is reflecting this trend. Under these conditions, it can be difficult to know where to turn for reliable, applicable advice.